2021
DOI: 10.1002/advs.202103343
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal CD68+F4/80+ Macrophages Are Mechanosensitive for Cortical Bone Formation by Secretion and Activation of TGF‐β1

Abstract: Mechanical force regulates bone density, modeling, and homeostasis. Substantial periosteal bone formation is generated by external mechanical stimuli, yet its mechanism is poorly understood. Here, it is shown that myeloid‐lineage cells differentiate into subgroups and regulate periosteal bone formation in response to mechanical loading. Mechanical loading on tibiae significantly increases the number of periosteal myeloid‐lineage cells and the levels of active transforming growth factor β (TGF‐β), resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…The results showed that five genes were significantly up-regulated in the CeO 2 @BSA group (Figure E), which was consistent with the sequencing results. TGF-β1 belongs to the TGF-β subfamily, which regulates cell growth and differentiation . The expression level of TGF-β1 protein was increased after CeO 2 @BSA treatment, which indicated that the TGF-β signaling pathway was indeed activated (Figure E).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The results showed that five genes were significantly up-regulated in the CeO 2 @BSA group (Figure E), which was consistent with the sequencing results. TGF-β1 belongs to the TGF-β subfamily, which regulates cell growth and differentiation . The expression level of TGF-β1 protein was increased after CeO 2 @BSA treatment, which indicated that the TGF-β signaling pathway was indeed activated (Figure E).…”
Section: Resultsmentioning
confidence: 93%
“…TGF-β1 belongs to the TGF-β subfamily, which regulates cell growth and differentiation. 62 The expression level of TGF-β1 protein was increased after CeO 2 @BSA treatment, which indicated that the TGF-β signaling pathway was indeed activated (Figure 3E). Thus, the TGF-β signaling pathway may mediate CeO 2 @BSA-induced bone differentiation of hPDLCs.…”
Section: ■ Introductionmentioning
confidence: 87%
“…Macrophages were isolated from the bone marrow of mice according to a previously described method and were cultured in CCM. 42,43 Mouse macrophage colony-stimulating factor (M-CSF; 20 ng/mL; Peprotech Inc., Rocky Hill, NJ, USA) was added to the CCM for 6 days prior to the experiment. SC cells were isolated from the sciatic nerve segments of neonatal Sprague−Dawley (SD) rats and cultured in CCM with no more than two passages prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…[92] Furthermore, in an mTBI model, repetitive mechanical impact has been shown to induce reactive astrogliosis and glial scar formation. [93] While it is believed that mechanical cues coregulate the phenotype and phagocytosis of macrophages, [94][95][96] how these cues affect microglia functions under the altered brain mechanical microenvironment after TBI needs to be further elucidated. Those microglia and astrocyte mechanobiology will be conducive to our understanding of the chronic consequences of TBI from a braininflammation perspective.…”
Section: Neuroinflammatory Responsesmentioning
confidence: 99%